(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
Your life goal is one of the main motivational goals of your life - the reasons why you get up in the morning. Goals can control life decisions, influence behaviors, shape goals, offer a sense of direction, and create meaning. For some people, the goal is career-related - meaningful, satisfying work. For others, their goal is to be accountable to their family or friends. Others seek meaning through spirituality or religious belief. Some people can clearly articulate their goals in all aspects of life.